Application of distributed combustion technique to hydrogen-rich coal gases: A numerical investigation. (29th January 2020) - Karyeyen, Serhat; Ilbas, Mustafa
Abstract: Distributed combustion has been a promising combustion technique, for enabling a more uniform thermal field, resulting in ultra-low pollutant emissions, reduced combustion noise, and enhanced combustion efficiency. This work examines combustion of hydrogen-rich coal gases derived from Turkish coal under distributed combustion conditions. Focus here is on obtaining a broadened flame and reducing pollutant emissions. Numerical modelling was carried out using a commercial code in order to predict the thermal field and pollutant emissions of the hydrogen-rich coal gases under distributed combustion conditions. A gas mixture (90% N2 and 10% CO2 ) was utilized to simulate controlled entrainment of hot reactive product gases into the fresh mixture prior to ignition in order to seek distributed combustion. The results showed that distributed combustion provided far more uniform thermal field that resulted in greatly reduced NOx emissions. The results also showed that the temperature difference between the maximum and exit temperature was reduced to approximately 200 K under distributed conditions. In addition, the NOx pollutant emissions predicted for each gas were reduced to near zero levels under high intensity distributed combustion conditions supporting the available experimental data. It has been concluded that enhanced thermal field uniformity and significantly reduced NOx emissions were achieved for hydrogen-rich coal gases under distributed conditions. Highlights: Hydrogen-rich coal gases have been investigated. Conventional and distributed combustion conditions have been compared. More uniform thermal field has been obtained. Reduced NOx emissions have been reached.